Chandra centres for COSMOS X-ray galaxy groups: differences in stellar properties between central dominant and offset brightest group galaxies. Issue 3 (27th November 2018) - Gozaliasl, Ghassem; Finoguenov, Alexis; Tanaka, Masayuki; Dolag, Klaus; Montanari, Francesco; Kirkpatrick, Charles C; Vardoulaki, Eleni; Khosroshahi, Habib G; Salvato, Mara; Laigle, Clotilde; McCracken, Henry J; Ilbert, Olivier; et al.
ABSTRACT: We present the results of a search for galaxy clusters and groups in the ∼2 deg 2 of the COSMOS field using all available X-ray observations from the XMM–Newton and Chandra observatories. We reach an X-ray flux limit of$3× 10^{-16} \, \mathrm{erg\, cm^{-2}\, s}^{-1}$ in the 0.5–2 keV range, and identify 247 X-ray groups with$M_{ 200c}=8× 10^{12}\text{--}3× 10^{14}\, M_{\odot }$ at a redshift range of 0.08 ≤$z$ < 1.53, using the multiband photometric redshift and the master spectroscopic redshift catalogues of the COSMOS. The X-ray centres of groups are determined using high-resolution Chandra imaging. We investigate the relations between the offset of the brightest group galaxies (BGGs) from halo X-ray centre and group properties and compare with predictions from semi-analytic models and hydrodynamical simulations. We find that BGG offset decreases with both increasing halo mass and decreasing redshift with no strong dependence on the X-ray flux and SNR. We show that the BGG offset decreases as a function of increasing magnitude gap with no considerable redshift-dependent trend. The stellar mass of BGGs in observations extends over a wider dynamic range compared to model predictions. At$z$ < 0.5, the central dominant BGGs become more massive than those with large offsets by up to 0.3 dex, in agreement with model prediction. The observed and predicted log-normal scatter in the stellar mass of both low- and large-offset BGGs at fixed halo mass is ∼0.3 dex.